If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2.2+x(-3.4)x=-2.5
We move all terms to the left:
2.2+x(-3.4)x-(-2.5)=0
We add all the numbers together, and all the variables
x(-3.4)x+4.7=0
We multiply parentheses
-3.4x^2+4.7=0
a = -3.4; b = 0; c = +4.7;
Δ = b2-4ac
Δ = 02-4·(-3.4)·4.7
Δ = 63.92
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-\sqrt{63.92}}{2*-3.4}=\frac{0-\sqrt{63.92}}{-6.8} =-\frac{\sqrt{}}{-6.8} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+\sqrt{63.92}}{2*-3.4}=\frac{0+\sqrt{63.92}}{-6.8} =\frac{\sqrt{}}{-6.8} $
| x/3−7=12 | | x3−7=12 | | .5(3x+6)=0.1-(x-3) | | 14o1/14=1 | | -2(4+6x)-8x=12 | | 7c=4c-12 | | 3x+4-x=5-10-x | | −3x+7=−9+5x | | 7c=4c | | -5+n/16=-6 | | −3x+13=−11+3x | | 11b+3=7b | | e-5=17+13 | | 4+5x=4x+9 | | 8x-2=-9+7x. | | 9a=4+a | | y=1.2-10-3.8 | | F(x)=4(2)^2 | | 6b+8b=75 | | 27-4a=a+12 | | -2f+2=-6 | | 30-22=4r | | 2/p^2=3/14 | | 6v+27=15 | | x²+5x+1600=0 | | (4x-7)=(5x-16) | | 3+10+9j=–3+9j | | -5(5.25+3.1x)=-6.2(2.5x+11.9) | | 60=4x-3+2x+24 | | 0.14x+0.9(x-5)=0.01(5x-3) | | 4x-18x=-3 | | 3x+3=11+2x-1 |